THE DECENT PERSON (MEMORIES OF L.G.FRIZMAN) - Криворучко, С. (New Collegium, 2020)
He left behind an aura of smiles, lightness, depth, aristocratic spirit. Leonid Henrykhovich belonged to those chosen people for whom science became a lifestyle. He never stopped trying to comprehend various phenomena of literature and history, and to find intersection points in completely outwardly different but internally similar categories, that is why he wrote every day. In the age of the Internet, contrary to widespread virtuality, the real, rather than electronic, mailbox of Leonid Henrykhovich continued to exist. It became a kind of allegory, a small but significant island from which Leonid Henrykhovich’s ability to help people, as a bridge, allowed young scholars to enter the world of great science. Leonid Henrykhovich was a gifted man, very disciplined in organizing his own creative process. He tried to write every day, for him it was equal to breathing. Leonid Henrykhovich was able to choose the profound words from a large number of banal stamps, bound by an endless set of texts, which created special musicality.